2024
DOI: 10.3390/antiox13040420
|View full text |Cite
|
Sign up to set email alerts
|

Curculigoside Attenuates Endoplasmic Reticulum Stress-Induced Epithelial Cell and Fibroblast Senescence by Regulating the SIRT1-P300 Signaling Pathway

Weixi Xie,
Lang Deng,
Rui Qian
et al.

Abstract: The senescence of alveolar epithelial cells (AECs) and fibroblasts plays a pivotal role in the pathogenesis of idiopathic pulmonary fibrosis (IPF), a condition lacking specific therapeutic interventions. Curculigoside (CCG), a prominent bioactive constituent of Curculigo, exhibits anti-osteoporotic and antioxidant activities. Our investigation aimed to elucidate the anti-senescence and anti-fibrotic effects of CCG in experimental pulmonary fibrosis and delineate its underlying molecular mechanisms. Our finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 78 publications
0
0
0
Order By: Relevance
“…Curculigoside, a phenolic glycoside compound, is the major biologically active ingredient present in Curculigo orchioides . Previous studies reported that curculigoside shows wide spread pharmacological activities including antioxidant ( 2 , 5 ), angiogenesis ( 6 ), neuroprotection ( 7 ) and anti-osteoporosis ( 8 ). Some earlier studies showed that curculigoside can protect endothelial cells against oxidative injury induced by H 2 O 2 , suggesting that this compound may constitute a promising intervention against cardiovascular disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Curculigoside, a phenolic glycoside compound, is the major biologically active ingredient present in Curculigo orchioides . Previous studies reported that curculigoside shows wide spread pharmacological activities including antioxidant ( 2 , 5 ), angiogenesis ( 6 ), neuroprotection ( 7 ) and anti-osteoporosis ( 8 ). Some earlier studies showed that curculigoside can protect endothelial cells against oxidative injury induced by H 2 O 2 , suggesting that this compound may constitute a promising intervention against cardiovascular disorders.…”
Section: Introductionmentioning
confidence: 99%